2011
DOI: 10.1158/1078-0432.ccr-10-2999
|View full text |Cite
|
Sign up to set email alerts
|

Expression of nm23-H1 Is Associated with Poor Prognosis in Peripheral T-Cell Lymphoma, Not Otherwise Specified

Abstract: Purpose: We examined whether nm23-H1 is a prognostic factor of peripheral T-cell lymphoma, not otherwise specified (PTCL-NOS).Experimental Design: We studied 102 consecutive, untreated PTCL-NOS patients from 1998 to 2008. The expression of nm23-H1 and TIA-1 was studied by immunohistochemistry.Results: nm23-H1 was positive in 44.1% and TIA-1 in 78.4% of the PTCL-NOS patients. nm23-H1 expression was not correlated with age, performance status (PS), lactate dehydrogenase (LDH) level, or stage but was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
(16 reference statements)
1
11
0
Order By: Relevance
“…Prior studies have explored and suggested tissuebased/ phenotypic prognostic markers for PTCL-NOS including proliferation gene signature or markers, 24,25 TP53 expression, 26 Epstein-Barr virus RNA, 27 the metastasis- suppressor gene product nm23-H1, 28 CCR4, 29 VEGF mRNA, 30 and FOXP1. 31 Although not a primary goal of the study, use of our immunophenotypic panel may also provide information on prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have explored and suggested tissuebased/ phenotypic prognostic markers for PTCL-NOS including proliferation gene signature or markers, 24,25 TP53 expression, 26 Epstein-Barr virus RNA, 27 the metastasis- suppressor gene product nm23-H1, 28 CCR4, 29 VEGF mRNA, 30 and FOXP1. 31 Although not a primary goal of the study, use of our immunophenotypic panel may also provide information on prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nm23 and HER-2 were negatively correlated with tumor metastasis and prognosis. Interestingly, HER-2 has been exploited as a promising candidate for peptide-based cancer vaccines (Kedrin et al, 2009;Lekka et al, 2010;Niitsu et al, 2011). PTEN, p53, and c-myc, which are all well known to play important roles in carcinogenesis, have also been shown to be associated with prognosis (Schade et al, 2009;Chen et al, 2011;Huang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, nm23 and HER-2 were negatively correlated with tumor metastasis and prognosis. Notably, HER-2 has been exploited as a promising candidate for peptide-based cancer vaccines (9)(10)(11)(12). PTEN, p53, and c-myc, which are all well known to play important roles in carcinogenesis, have also been shown to be associated with prognosis (13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%